Pendampingan Peningkatan Kinerja Karyawan dan Pemahaman Analisis Resiko pada UD. Mekar Mojokerto - Kasnowo, Kasnowo; Armin, Rini; Setiono, Hari; Bahril Ilmiddaviq, Muhammad (BADAN PENERBIT STIEPARI PRESS, 2025)
UD. Mekar is a snack producer known for its popular brand “2Koki Ikan Tengiri,” renowned for its high-quality and savory mackerel fish crackers. Although operating as a home-based industry, UD. Mekar holds significant potential to reach broader markets. This community service initiative involved lectures, discussions, and Q&A sessions focusing on two crucial aspects: employee performance improvement and business risk analysis. The results indicate that employees demonstrate a high level of enthusiasm toward becoming professional workers, despite being in the home industry sector. However, their understanding of business risk remains limited to technical aspects, highlighting the need for broader risk awareness, including operational, financial, and marketing risks. This activity serves as an initial step toward formulating strategies for enhancing employee performance, implementing risk mitigation, and planning for continuous training. The strategic approach is expected to strengthen UD. Mekar's competitiveness and support the national market expansion of its products.